2015
DOI: 10.1097/ico.0000000000000344
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Oculus Pentacam Tomographer Measurements in Patients With Keratoconus

Abstract: Pentacam measurements show increased variability in patients with keratoconus. The degree of variability correlates with TA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
2
19
0
1
Order By: Relevance
“…This finding is consistent with the recent report by Vianna et al 16 of increased variability in certain measures with Pentacam in patients with high topographic astigmatism.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with the recent report by Vianna et al 16 of increased variability in certain measures with Pentacam in patients with high topographic astigmatism.…”
Section: Discussionsupporting
confidence: 93%
“…The precision of measurements in our study was found to be best for the Pentacam HR, and better in healthy than in keratoconic eyes, which is in line with previous studies 24,25 . Intra-observer agreement was generally better than inter-observer agreement in both groups, which is also consistent with previous studies 15,25 .…”
Section: Discussionsupporting
confidence: 93%
“…Some variability exists in repeat measurements in keratoconic eyes using the same imaging device,25 and mild variability exists when imaging both keratoconic and normal corneas when using different devices 26. For these reasons, we cannot completely extrapolate our findings to other studies using different imaging technology, and we chose to report the CIs specifically to provide some sense of the possible variability that could exist.…”
Section: Discussionmentioning
confidence: 99%